Aspergillus mastoiditis in an immunocompetent patient: A case report and review of the literature. (April 2014) - Youssef, Mona; Bassim, Marc; Shabb, Nina; Kanj, Souha S.
Abstract Aspergillus mastoiditis usually occurs in immunocompromised patients. There are a few isolated reports in the literature involving immunocompetent patients. We hereby describe the case of an immunocompetent patient diagnosed with invasive Aspergillus mastoiditis, which was treated successfully, and review the literature pertaining to this condition. The common clinical presentations, putative pathophysiology, and recommended therapy are discussed.